Major Inhibitors to Female Formal Labour Force Participation in Selected Towns of Awka South Local Government Area, Anambra State, Nigeria - Nwokoye, Ebele Stella (NIU Journal of Social Sciences, 2017)
The long tradition of relegating women to household chores and nurturing of children has resulted in the low rate of women participation in the labour force of most developing countries, yet women have often been referred to as the bedrock of families and are also as certified as the male counterparts. This paper therefore sought to find out the major factors that hinder women from actively participating in the formal labour market in Awka South Local Government Area of Anambra state, Nigeria. This study is based on the neoclassical work/leisure trade-off model and Beckerâ€™s human capital theory, and adopted the non-probability sampling technique. Simple statistics approach using tables, chart, frequencies, percentages and bar charts were used to analyze the responses of the respondents gathered through a well-structured questionnaire with the response options are agreed (A), strongly agreed (SA), disagree (D), strongly disagree (SD) and not sure (NS). The major inhibiting factors were found to be job mismatch, unattractive wage, an adequate source of income, career satisfaction and not being the head of the family. This conclusion was arrived at based on the percentage of the strongly agreed option and further confirmed with the result of the One-Sample t-test. The major recommendation, drawn from both the questionnaire responses and in-depth interview, is that the government should create employment agencies where employers could reach out to their prospective employees and the unemployed can locate the suitable jobs for themselves. Key words : Awka, employees, female, formal, labour force participation, labour market,     Nigeria